IMPLEMENTASI PROGRAM APLIKASI SISTEM PEMANTAUAN MASYARAKAT (SITASYA) DI KOTA MANADO - SANGALA, REGITA JENIVER; LENGKONG, FLORENCE DAICY; KOLONDAM, HELLY (Sam Ratulangi University, 2020)
This study aims to determine the implementation of the Community Monitoring System ApplicationProgram in Manado City. The research method used is descriptive qualitative. Qualitative descriptiveresearch is a research that aims to describe and describe events and phenomena that occur in the field. Datacollection was carried out by observation and interview techniques. The results show that based on the theoryof policy implementation there are three activities that affect the policy implementation process, namelyOrganization, Interpretation, and Application, seen from these three activities, the implementation of thecommunity monitoring system application program in the city of Manado is not going well and in the processthere are still some obstacles in the implementation of programs implemented by the Manado CityInformation and Communication Office.Keywords: Implementation, Program, Smart City, Sitasya